Evaluation of Plasma Membrane Integrity of Sperm and Fertility of Post Thawed Frozen Semen of Black Bengal Goat - Ahmed, Imtiaz; Akhtar, Mahomudha; Akter, Tasmina; Akter Mohammad Yahia Khandoker, Mobarak (The Indian Journal of Animal Reproduction, 2026)
The study aimed to evaluate and compare the effectiveness of different freezing durations in combination with three semen diluents (Triladyl, Andromed, and Tris-citrate) on sperm plasma membrane integrity and fertility of post-thawed semen in Black Bengal goats. Data on frozen semen production and evaluation were collected over a period of six months. Post-thawed semen samples were obtained according to the specified freezing times and diluents, and sperm plasma membrane integrity was assessed using the Hypo-osmotic Swelling Test (HOST). In this study, 3 freezing times (F1 = Freezing time 15 minutes, F2 = Freezing time 20 minutes, and F3 = Freezing time 25 minutes) were used in an ice box filled with liquid nitrogen (LN) vapor. After freezing with 3 different freezing times and 3 diluters, F1 showed sperm motility ranged from 20.3±1.33% to 53.7±.88%. A significant effect (p<0.0001) on sperm motility was found among the F1 freezing time and diluter groups. F2 showed sperm motility ranged from 24.0±1.03% to 43.7±.88%, freezing time and diluter groups both had a statistically significant effect (p<0.0001) on sperm motility. F3 freezing rate showed motility ranged from 30.3±1.05% to 34.8±1.45%. The F3 freezing time and diluter groups also had a significant effect (p<0.05) on sperm motility. For sperm plasma membrane integrity, F1 showed the highest result for Triladyl diluter (67.8 ±.61%) and a level of significant effect (p<0.0001) was found among the freezing time and the diluter groups. F1 and Triladyl diluter group also showed higher coiling rates on the HOS test. A positive correlation was observed between sperm that had swelled under the HOS test and motility. Finally, a better conception rate was observed with the F1 and Triladyl diluter group. So the result of these studies revealed that cryopreservation of Black Bangal goat semen with freezing within 15 minutes (F1) and Triladyl diluter group offers better sperm plasma membrane integrity and post-thawed semen fertility